KONSEP PENDIDIKAN AKHLAK PERSPEKTIF BUYA HAMKA DALAM MENJAWAB ISU-ISU AKTUAL PENDIDIKAN KONTEMPORER - Arifin, Muhammad Fikri (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
This research seeks to answer moral problems by examining the concept of moral education from Buya Hamka's perspective and its relevance to contemporary educational issues. This research is based on library research, using works about Hamka as the main source, and analyzing data through descriptive, and interpretation techniques. The results show that Hamka's concept of moral education does not only focus on cognitive aspects, but also emphasizes character building that is reflected in daily life. The values analyzed include: (a) religious values, such as piety, tawakal, gratitude, repentance, patience, honesty, and sincerity; (b) social care values, such as trustworthiness, generosity, justice, and ihsan; and (c) ethical education, including self-control, responsibility, and high fighting spirit. This concept is also relevant to respond to contemporary Islamic education issues, such as digitalization transformation, improving the quality of educators through training and professional development, mental health that includes self-control and relationship with Allah, and strengthening the character of students. Thus, Hamka's concept offers a holistic solution to build the morals of a generation with faith and strong character.